“Real impact”: Challenges and opportunities in bridging the gap between research and practice – Making a difference in industry, policy, and society - Dwivedi, Yogesh K.; Jeyaraj, Anand; Hughes, Laurie; Davies, Gareth H.; Ahuja, Manju; Albashrawi, Mousa Ahmed; Al-Busaidi, Adil S.; Al-Sharhan, Salah; Al-Sulaiti, Khalid Ibrahim; Altinay, Levent; Amalaya, Shem; Archak, Sunil; et al. (My University, 2024)
Achieving impact from academic research is a challenging, complex, multifaceted, and interconnected topic with a number of competing priorities and key performance indicators driving the extent and reach of meaningful and measurable benefits from research. Academic researchers are incentivised to publish their research in high-ranking journals and academic conferences but also to demonstrate the impact of their outputs through metrics such as citation counts, altmetrics, policy and practice impacts, and demonstrable institutional decision-making influence. However, academic research has been criticized for: its theoretical emphasis, high degree of complexity, jargon-heavy language, disconnect from industry and societal needs, overly complex and lengthy publishing timeframe, and misalignment between academic and industry objectives. Initiatives such as collaborative research projects and technology transfer offices have attempted to deliver meaningful impact, but significant barriers remain in the identification and evaluation of tangible impact from academic research. This editorial focusses on these aspects to deliver a multi-expert perspective on impact by developing an agenda to deliver more meaningful and demonstrable change to how “impact” can be conceptualized and measured to better align with the aims of academia, industry, and wider society. We present the 4D model - Design, Deliver, Disseminate, and Demonstrate - to provide a structured approach for academia to better align research endeavors with practice and deliver meaningful, tangible benefits to stakeholders.
Keywords: Academic impact; Implications for practice; Relevance; Research benefits; Research contribution; Research impact